2022
DOI: 10.1007/s40487-022-00212-5
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Outcomes of Belantamab Mafodotin for Relapsed/Refractory Multiple Myeloma (RRMM): Preliminary Results of a Spanish Expanded Access Program (EAP)

Abstract: Introduction Belantamab mafodotin (BM) is a new anti-BCMA antibody–drug conjugate, recently approved for triple-class relapsed and refractory multiple myeloma (RRMM). We assessed real-world outcomes with BM in patients under the Spanish Expanded Access Program (EAP). Methods We conducted an observational, retrospective, multicenter study including RRMM patients who received ≥ 1 dose of BM (Nov 2019 to Jun 2021). The primary endpoint was overall response rate (ORR). Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…Overall, the results of DREAMM‐2 have meaningfully informed ongoing and future studies of belamaf: patients who respond demonstrate rapid responses that are sustained for long durations. These results have translated into clinical practice, where similar real‐world results have been reported 14,19,38 …”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Overall, the results of DREAMM‐2 have meaningfully informed ongoing and future studies of belamaf: patients who respond demonstrate rapid responses that are sustained for long durations. These results have translated into clinical practice, where similar real‐world results have been reported 14,19,38 …”
Section: Discussionsupporting
confidence: 75%
“…In this real‐world study, patients who were refractory to anti‐CD38 mAbs had a median OS of 8.6 months, with OS ranging from 11.2 months for patients not simultaneously refractory to an immunomodulatory agent and a PI, to 5.6 months for penta‐refractory patients 6 . Additional real‐world studies have demonstrated similar findings, consistent with the clinical trial setting 15–19 …”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Belantamab mafodotin BCMA-targeted therapy has been considered a potential “off-the-shelf” drug that can be administered immediately in an outpatient setting. Real-world data have reported outcomes comparable with the DREAMM-2 trial in terms of objective response rate (33-45%), median progression-free survival (PFS) (2-6.5 months), and median overall survival (OS) (6-18 (not-reached) months) [ 12 - 14 ]. However, we did not see a similar response in our patients, as they did not respond to belantamab mafodotin treatment, and their disease rapidly progressed.…”
Section: Discussionmentioning
confidence: 99%